Environmental impact assessment of the manufacturing of a commercial aircraft - Kolios, Athanasios; Asproulis, Nikolaos; Howe, Stuart; Salonitis, Konstantinos (Cranfield University Press, 2013)
This paper documents the methodology and presents the results of a comprehensive LCA study of an Airbus A320 commercial airliner to determine the relative environmental impact of its manufacturing phase. The study was conducted in accordance with ISO 14040/44 using SimaPro LCA software, the EcoInvent inventory database and Eco-Indicator 99 weighting method, which allows the analysis to be outputted in a single score representing a number of damage models including damage to human health, ecosystem quality or resource depletion. Results indicate CFRP wings to have the most significant contribution to the overall environmental impact as a proportion to mass.
Keywords: LCA; Aviation; Airliners